From Trust to Sustainability: A Systematic Literature Review of the Role of Islamic Accountability Accounting in Organizational Transformation - Faizah Dani Pragita; Febri Maulana; Ichfan Al Mutaqin; Intan Puspita Sari; Rustam Hanafi (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the role of Islamic accountability accounting in supporting organizational transformation toward sustainability through a Systematic Literature Review (SLR) approach. The study is motivated by the limitations of conventional sustainability accounting, which tends to emphasize economic performance, efficiency, and organizational legitimacy while paying limited attention to ethical, moral, and spiritual dimensions. Using the PRISMA 2020 framework, this study systematically identifies, evaluates, and synthesizes relevant literature on Islamic accountability accounting, sustainability accounting, maqashid al-shariah, Islamic sustainability reporting, and Islamic green accounting. A total of 30 journal articles were selected and analyzed through thematic analysis to identify major concepts, research developments, and future research opportunities. The findings reveal that Islamic accountability accounting has evolved from a narrow economic accountability perspective into a multidimensional accountability framework based on the values of amanah, justice, balance, and maslahah. The literature indicates that the integration of maqashid al-shariah and sustainability accounting provides a broader understanding of organizational sustainability by incorporating economic, social, environmental, and spiritual dimensions. Furthermore, Islamic sustainability reporting and Islamic green accounting have the potential to become instruments of organizational transformation by strengthening governance, transparency, and responsible resource management. However, existing studies remain predominantly focused on Islamic financial institutions, highlighting the need for further empirical research in other sectors and the development of an Islamic Sustainability Accountability Framework. This study contributes theoretically by expanding the sustainability accounting paradigm through Islamic values and practically by providing insights for organizations seeking to build more ethical and sustainable accountability systems.